Towards precision pain medicine for pain after cancer: the Cancer Pain Phenotyping Network multidisciplinary international guidelines for pain phenotyping using nociplastic pain criteria. (May 2023) - Nijs, Jo; Lahousse, Astrid; Fernández-de-las-Peñas, César; Madeleine, Pascal; Fontaine, Christel; Nishigami, Tomohiko; Desmedt, Christine; Vanhoeij, Marian; Mostaqim, Kenza; Cuesta-Vargas, Antonio I.; Kapreli, Eleni; Bilika, Paraskevi; et al.
Summary: Pain after cancer remains underestimated and undertreated. Precision medicine is a recent concept that refers to the ability to classify patients into subgroups that differ in their susceptibility to, biology, or prognosis of a particular disease, or in their response to a specific treatment, and thus to tailor treatment to the individual patient characteristics. Applying this to pain after cancer, the ability to classify post-cancer pain into the three major pain phenotypes (i.e. nociceptive, neuropathic, and nociplastic pain) and tailor pain treatment accordingly, is an emerging issue. This is especially relevant because available evidence suggests that nociplastic pain is present in an important subgroup of those patients experiencing post-cancer pain. The 2021 International Association for the Study of Pain (IASP) clinical criteria and grading system for nociplastic pain account for the need to identify and correctly classify patients according to the pain phenotype early in their treatment. These criteria are an important step towards precision pain medicine with great potential for the field of clinical oncology. Within this framework, the Cancer Pain Phenotyping (CANPPHE) Network, an international and interdisciplinary group of oncology clinicians and researchers from seven countries, applied the 2021 IASP clinical criteria for nociplastic pain to the growing population of those experiencing post-cancer pain. A manual is provided to allow clinicians to differentiate between predominant nociceptive, neuropathic, or nociplastic pain after cancer. A seven-step diagnostic approach is presented and illustrated using cases to enhance understanding and encourage effective implementation of this approach in clinical practice.